Adaptation of Siyasah Fiqh as a Strategy to Prevent Money Politics in Elections - Hilmi Ridho; Aizat Khairi; Abdul Mujib; Sageer Ahmed (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2024)
One of the election violations that often occurs during the run-up to general elections in Indonesia is the rampant practice of money politics. In the 2024 elections, 29 provinces are prone to cases of money politics with a moderate category level and 5 provinces with a high level of vulnerability. The purpose of this research is to find out the forms and main factors of money politics, to analyze whether money politics is the same as bribery (risywah) in Islamic law and its framework, and to find out the role and strategy of Bawaslu in preventing the practice of money politics in the run-up to the election. This research method uses normative legal research, which is a process for finding legal rules, legal principles, and legal doctrines to answer the legal issues at hand. The conclusion of this research shows that the form of money politics can be in the form of money, goods, and services. The main factors are influenced by the thirst for glory, the low economy of the community, the lack of knowledge about politics, and the strength of tradition. According to fiqh siyasah, the practice of money politics includes the act of risywah (bribery) based on the Qur'an, Hadith, and the opinions of scholars. Four strategies must be carried out by Bawaslu, namely; first, overseeing the election and reporting when violations occur. Second, coordinate with internal and external parties. Third, conduct offline and online socialization about the dangers of money politics. Fourth, reconstructing the regulation of criminal acts of money politics that have a deterrent effect, disqualifying election participants, giving strict sanctions to the success team, and providing guarantees of protection and rewards to the reporter.